Extracorporeal photopheresis for graft versus host disease: Identifying a clinical pathway and associated resource utilization. Issue 3 (28th November 2017) - Yerrabothala, Swaroopa; Talebian, Laleh; Klinker, Karen; Hickman, Joshua; Hill, John M.; Hayes, Christi; Lowrey, Christopher; Szczepiorkowski, Zbigniew M.; Meehan, Kenneth R.
Abstract : Extracorporeal photopheresis (ECP) is an established therapy for the treatment of graft‐versus‐host‐disease (GVHD) following an allogeneic stem cell transplant. We performed a prospective analysis of patients receiving ECP treatment for GVHD to identify a clinical pathway and resource utilization of this process. The cohort included consecutive allogeneic stem cell recipients with GVHD. ECP was performed using the CELLEX Photopheresis System or the UVAR XTS Photopheresis System (Therakos, Inc, Exton, PA). A clinical pathway was developed and a time and motion study was conducted to define the resource utilization and costs associated with ECP. Patients were treated with either CELLEX (n = 18 procedures) or UVAR ( n = 4 procedures). Total time commitment for each procedure for the 2 machines differed. The time for ECP was 117 min (median, range: 91‐164 min) using CELLEX and 161 min (median; range: 140‐210) using the UVAR‐XTS machine. Total costs of each ECP procedure were 3420.50. There is a considerable time commitment of the patient and the clinical staff when employing ECP to treat GVHD. ECP costs are significant considering this is a prolonged therapy continued for several months. With this finalized pathway and costs, we have a standardized clinical pathway for the treatment of GVHD. We are addressing minimizing resource utilization while emphasizing quality care for these patients.